Evaluating the Economic Efficiency of Fuel Reduction Treatments in Sagebrush Ecosystems That Vary in Ecological Resilience and Invasion Resistance - Thomas A. Bridges-Lyman; Jessi L. Brown; Jeanne C. Chambers; Lisa M. Ellsworth; Matthew C. Reeves; Karen C. Short; Eva K. Strand; Michael H. Taylor (Land)
The concepts of resilience and resistance (R&R) have been used to improve wildland fuel treatment outcomes by identifying parts of the landscape that are more likely to respond well to treatment. This study examined how the economic benefits and costs of fuel treatments in sagebrush (Artemisia spp.) ecosystems varied with the resilience and resistance properties of the treatment site. Generalized ecological models were developed for the economic analysis of fuel treatments that integrated ecological succession, annual grass invasion, pinyon–juniper expansion, and wildfire to simulate ecosystem dynamics over time. The models incorporated resilience and resistance by varying model parameters related to each plant community’s ability to resist annual grass invasion and recover post-disturbance. Simulations produced estimates of the expected (ex ante) benefit–cost ratio for each treatment. The approach also considered the benefits associated with the system remaining in an ecologically favorable condition, allowing us to report a more holistic measure of the net economic benefits of fuel treatments. The results from the simulations indicated fuel treatment was economically efficient in late-successional sagebrush and early-successional juniper in mountain big sagebrush associations. For sagebrush associations where treatment was economically efficient, higher R&R status sites had higher benefit–cost ratios. The results suggested that treatment costs were more determinative of economic efficiency than treatment benefits.